COMPUTER-MEDIATED COMMUNICATION, ORGANIZATIONAL STRUCTURE AND CLIMATE TO INCREASE COMMITMENT IN KNOWLEDGE SHARING PROCESS: A RESEARCH FRAMEWORK - ima dwitawati (Prodi Teknologi Informasi UIN Ar-Raniry Bekerjasama dengan Pusat Penelitian dan Penerbitan LP2M Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This research presented a research framework to study the computer mediated communication, organizational structure and climate to growth effective commitment as an attitude in knowledge sharing process. Its starting by the exploration of organization commitment and importance, following by putting the computer mediated communication, organizational structure, and climate and put this three components as independent variable. Then, continue by exploring the dependent variable in this research is organizational commitment in knowledge sharing process. The result is a research framework of this area which can be used to explore an actual case in an organization in various industries.